Analysis of Overload on Highway Pavement Construction : A Case Study of Road Damage on KH. Ahmad Dahlan Street, East Lombok Regency - R T Darmawan, Lutfi, Syakirin (Jurnal Handasah, 2025)
Soil used with a low CBR value will produce a construction that is not optimal results (quickly damaged). For this reason, if a construction is to be used, the CBR value  should be increased to be able to withstand the load on it. One way to improve the quality of  soil is by means of stabilization. In this study the stabilization method used is chemically with added ingredients in the form of a mixture of rice husk ash and lime. This study was conducted by adding 6% husk ash and 5%, 10% and 15% lime from the dry weight of soil. Physical properties tests conducted include moisture content, specific gravity, grain size distribution and Atterberg limits. While mechanical tests include compaction test proctor, and CBR with curing period for 0 days, 7 days and 14 days. From the original soil test results obtained unsoaked CBR value of 3.7% while for soaked CBR of 3.1%, with a value of Gs=2.75, yd = 1.39 gr/cm3 at Wopt = 30%. The addition of stabilizer material can affect the CBR value.The addition of stabilizer material 6% rice husk ash + 15% lime is the best mixture. For CBR unsoaked increased from 3.7% to 23.25%. As for the value of CBR soaked increased from 3.1% to 17.11% or has exceeded the value of CBR soaked standards set by Highways by 6%